Technology of the Gramophone Records of the Music Museum by Fourier Transform Infrared Spectrometry (FTIR) Method - Afzali, Seyedeh Zeinab; Mokhtabad, Seyed Abdulhossein (Journal of History Culture and Art Research, 2017)
Music is one of the branches of the art whose helpful role and usefulness in the human’s mind and soul is undeniable. It is the only art which in the philosophers’ divisions is directly linked with the human spirit and immediate overflows the ears of his soul. The sound, as a psychological phenomenon is associated with the emotion and excitement so that sometimes calms and sometimes confuses the human. This study aims to examine the technology of the gramophone records in the Music Museum by Fourier transform infrared spectrometry (FTIR). The method of this research is experimental and the data are collected by documentation, library, and using FTIR tests. Some records of the Music Museum were studied including four samples of 78 rpm platter (stone platter), one sample of 45 rpm, and one sample of 33 rpm (vinyl platter). The results of the FTIR test indicated that the materials of the records were vinyl and shellac and in their raw material, some of the softening additives (phthalates) and fillers (silica and calcium carbonate compounds) had been used.